Fra konstituerende magt til destituerende magt:: En kritik af Agambens konception af magt og politik - Eggers, Nicolai von (Slagmark - Tidsskrift for idéhistorie, 2015)
The Italian philosopher Giorgio Agamben’s conception and critique of sovereignty has won him wide and well-deserved acclamation. In this article, however, it is argued that Agamben’s conception of sovereignty is somewhat misplaced, and, as a consequence, his positive political project of developing a ‘destituent power’ (as opposed to constituent power) is highly deficient in terms of construing a popular and viable political alternative. The critique of Agamben is developed through a close reading of Aristotle’s Politics and his notion of kurion. It is argued that Agamben’s flawed conception of sovereignty reemerges symptomatically in his extremely problematic reading of Aristotle’s Politics, and that a viable political alternative to both Agamben’s own project and the conception of politics that he criticizes can be developed through an alternative and closer reading of Aristotle.